Radioprotective properties of sodium humate in radiation-induced mutagenesis in cultured lymphocytes of thyroid cancer patients - Shkarupa, V.M.; Klymenko, S.V. (Experimental Oncology, 2016)
Aim: To investigate the effect of sodium humate on the level of cytogenetic damage in culture of lymphocytes of patients with thyroid cancer after γ-irradiation. Materials and Methods: Metaphase analysis of chromosome aberrations in cultured peripheral blood lymphocytes of 10 individuals with thyroid cancer was performed after irradiation of lymphocytes in vitro at a dose of 1 Gy from ¹³⁷Cs source at the early G₀ phase of cell cycle. Sodium humate was added to cell culture for 30 ± 15 min after phytohemagglutinin stimulation at concentrations of 10 and 100 μg/ml. Results: Sodium humate exhibited antimutagenic properties. The preparation at a concentration of 10 μg/ml was more effective than at a concentration of 100 μg/ml, reducing the average incidence of radiation-induced chromosome aberrations by 51.88 and 38.77%, respectively. The most pronounced antimutagenic effect of sodium humate was the reduction of the frequency of chromosomal type aberrations, however, such efficiency varied between individual patients with thyroid cancer. Conclusions: Sodium humate could be considered as a potential therapeutic modifier of radiation damage.